Suicide contagion : is the media placing the public at risk? An analysis of suicide reporting in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Palmerston North, New Zealand - Colhoun, Craig (Massey University, 2016)
The media’s reporting of suicide has been shown to increase subsequent community suicide rates through a process called suicide contagion. It is not necessarily the reporting of suicide that causes suicide contagion, but rather it is the manner in which it is reported. As a result, within New Zealand a number of legislative (the Coroners Act, 2006) and industry guidelines (Reporting Suicide: A resource for the media, 2011) have been introduced to decrease any risk of suicide contagion. The aim of the present study was to investigate how suicide is portrayed in newspapers, examine whether suicide reporting has changed between two timeframes, and explore journalists’ beliefs and behaviour about suicide reporting. The present thesis is divided into two parts. Study One uses quantitative and qualitative methods to compare and contrast all suicide newspaper articles from leading New Zealand newspapers from 12 month periods in 1997 (pre-suicide guidelines) and 2009 (post-suicide guidelines). The results revealed that reporting quality had improved where there was a decrease in the occurrence of elements known to contribute to suicide contagion. However, despite reporting quality improving the study identified that articles continued to include a number of areas where suicide reporting could be improved upon. Study Two complemented Study One by interviewing journalists about their knowledge of contagion, reporting practices and barriers and difficulties in suicide reporting. The rhetorical analysis demonstrated that participants argued that evidence for suicide contagion was inconclusive and problematic. This had important implications as the media argued their reporting was to a high standard and consequently did not view reporting guidelines or the Coroners Act as necessary. As a result, participants largely avoided these restrictions and viewed them as a threat to media freedom. Together these studies demonstrated that suicide reporting quality can still be improved, however, in order to improve writing styles, implementing suicide guidelines does not appear enough. Instead, this study demonstrates that it is necessary to increase media awareness of suicide contagion, so the media understand the importance of applying reporting guidelines.
Keywords: Suicide in mass media; Suicide; Risk factors; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology